Budownictwo obronne w Liber Benefioiorum Jana Długosza a realia archeologiczne - Marciniak, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
The article attempts to answer the question whether the notions: "curia militaris", "praedium unicum militare" and others used by Długosz in “Liber beneficiorum dioecesis Cracoviensis" mean dwelling houses of defensive character. This, some records chosen from the text of Liber beneficiorum were confronted to the results of archaeological investigations or compared to other historical sources. Among 401 objects in 344 places named by Długosz 86 ones are known to archaeologists and these were discussed in the article. Only 26 objects (6.5%) can be undoubtedly treated as defensive ones. As much as 47 objects require to be classified. 12 places were not localized. Hence, the problem put forward above should be left without answer hoping that future investigations with enlarged source basis will allow us to solve this problem.